The impact of foreign direct investment on the economy in developing countries - lukman hakim; Irham Fahmi (Jurnal Mantik, 2023)
Foreign Direct Investment (FDI) is a critical factor in shaping the economic development of developing countries. This study conducts a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) diagram to comprehensively assess the multifaceted impact of FDI on developing economies. The primary objective is to synthesize existing research and provide insights into the intricate relationship between FDI inflows and economic growth, industrialization, technological progress, job creation, and trade dynamics in these countries. Method: In April 2023, a rigorous search in the Scopus database yielded 93 relevant articles after filtering based on language (English) and time (2018-2023). Further refinement narrowed the focus to 61 publications on "investment and economy." Selecting only "Articles" as the document type resulted in 10 high-quality articles suitable for analysis. The findings highlight the diverse effects of FDI on the economic growth of developing nations, including its role as a catalyst for industrial development, technology transfer, productivity enhancement, job creation, and fostering trade integration. Understanding the potential benefits and challenges associated with FDI can empower policymakers and investors to make informed decisions, optimizing FDI's contribution to sustainable and inclusive economic development in developing countries. This literature review contributes to a deeper understanding of the complex relationship between FDI and economic growth, industrialization, technological advancements, job creation, and trade dynamics in these regions